2009
DOI: 10.1080/14767050802488212
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and penicillin tolerance in ano-vaginal group B streptococci

Abstract: The relatively high rates of resistance to four of the 15 antibiotics tested confirm that for women allergic to penicillin and colonised with GBS, antibiotic sensitivities should be determined. We noticed increasing resistance to clindamycin over a 7-year period. Ongoing surveillance of local antibiotic resistance patterns at the institutional level is important in determining optimal prophylaxis as resistance patterns differ between institutions and are increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…There is considerable evidence of increasing resistance of GBS to clindamycin and erythromycin in both the general population (4, 6) and among pregnant women (15,16). For example, investigators from Connecticut reported a 400% increase in GBS clindamycin resistance (from 5.3% to 21%) over a 7-year period from 2000 to 2007 (16,18). A 2010 study from Utah which reports relatively high rates of GBS resistance to erythromycin (44%) and clindamycin (24%) for isolates collected between 2007 and 2008 is the most recent study in the literature prior to our report (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is considerable evidence of increasing resistance of GBS to clindamycin and erythromycin in both the general population (4, 6) and among pregnant women (15,16). For example, investigators from Connecticut reported a 400% increase in GBS clindamycin resistance (from 5.3% to 21%) over a 7-year period from 2000 to 2007 (16,18). A 2010 study from Utah which reports relatively high rates of GBS resistance to erythromycin (44%) and clindamycin (24%) for isolates collected between 2007 and 2008 is the most recent study in the literature prior to our report (2).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in clindamycin resistance parallels the marked in- crease in methicillin-resistant Staphylococcus aureus (MRSA) and may be driven at least partly by the reported 300% increase in clindamycin use for the treatment of MRSA infections over the past decade (11). There is considerable evidence of increasing resistance of GBS to clindamycin and erythromycin in both the general population (4, 6) and among pregnant women (15,16). For example, investigators from Connecticut reported a 400% increase in GBS clindamycin resistance (from 5.3% to 21%) over a 7-year period from 2000 to 2007 (16,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is easy and simple and could be performed in most molecular laboratories with basic equipment. Although it cannot provide information on antibiotics sensitivity, almost all GBS were sensitive to ampicillin/penicillin, making the susceptibility test probably unnecessary in clinical practice [24,25]. Extensive analysis of GBS and ST-17 clone infection using this convenient multiplex PCR method may be beneficial to pregnant women with expectant prophylactic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although the S. agalactiae species remains sensitive to beta-lactams, the prevalence of the resistance to clindamycin and erythromycin has increased over recent years. 33 To assess the robustness of our results, we performed a sensitivity analysis using five scenarios. Indeed, the real cost of the tests vary around the cost given by the database of the University-Hospital of Montpellier, according to the manufacturers' fees.…”
Section: Discussionmentioning
confidence: 99%